3-O-Hydroxytyrosol glucuronide and 4-O-hydroxytyrosol glucuronide reduce endoplasmic reticulum stress in vitro. Issue 10 (4th August 2015) - Giordano, Elena; Dangles, Olivier; Rakotomanomana, Njara; Baracchini, Silvia; Visioli, Francesco
Abstract : Endoplasmic reticulum (ER) stress is important for atherosclerosis development and is mediated by the unfolded protein response (UPR). Abstract : Endoplasmic reticulum (ER) stress is important for atherosclerosis development and is mediated by the unfolded protein response (UPR). In this work, we synthesized two among the most physiologically-prominent hydroxytyrosol HT hepatic metabolites, i.e. 3- O -HT glucuronide and 4- O -HT glucuronide and we tested their activities on ER stress (in human hepatocarcinoma HepG2 cells), to gain further insight into the cardiopreventive properties of HT, extra virgin olive oil, and the Mediterranean diet. We report that 3- O -HT glucuronide and 4- O -HT glucuronide inhibit tunicamycin-induced ER stress. As compared with the effects of the parent molecule, 3- O -HT glucuronide and 4- O -HT glucuronide at 10 μM and 25 μM alone induced a milder change in mRNA expression levels of both CCAAT-enhancer-binding protein homologous protein (CHOP) and glucose regulated protein GRP78 immunoglobulin heavy chain binding protein (BiP). In conclusion, we add further evidence to the hypothesis that the HT intake might be atheroprotective and reiterate the usefulness to preferably use high-quality, high-(poly)phenol extra virgin olive oil as a prominent condiment.